Integrasi Pendidikan Agama Islam dengan Kecerdasan Emosional: Tinjauan Literatur atas Pengaruh Spiritualitas Dalam Pengembangan Kecerdasan Intrapersonal - Abdusshomad, Alwazir (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This study examines the relationship between Islamic Religious Education (PAI) and emotional intelligence, with a focus on intrapersonal intelligence through the impact of spirituality. Through a literature review, the study finds that PAI plays a significant role in the development of self-awareness, emotional regulation, and internal motivation. Religious teachings, such as patience and reliance on God (tawakal), help individuals manage their emotions and enhance their inner well-being. The findings indicate that PAI contributes not only to moral and social aspects but also to emotional and psychological development. The study recommends a comprehensive approach to religious education as an effective strategy for improving intrapersonal intelligence. Further research is needed to empirically assess the influence of PAI on emotional intelligence